2018
DOI: 10.1038/s41393-018-0069-z
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic patterns of the rat hindlimb in response to muscle stretch after spinal cord injury

Abstract: Study Design Experimental Study Objectives To characterize the specific hindlimb electromyographic (EMG) patterns in response to muscle stretch and to measure the applied forces during stretching in the rat model of moderate SCI. Setting Kentucky Spinal Cord Injury Research Center, Louisville, KY, USA Methods Female Sprague Dawley rats (n=4) were instrumented for telemetry-based EMG recording (right Rectus Femoris and Biceps Femoris) and received a moderate T10 spinal cord injury (SCI). The major hindlim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In 2018, Keller, et al [173] investigated the EMG patterns in hindlimb muscles of SCI rats that underwent a daily range-of-motion stretching therapy. After several consecutive days of stretching, locomotor ability declined, and EMG recordings revealed increased clonus-like contractions during stretching [173]. This irregular muscle firing due to the stretching may explain the emergence of the irregular stepping patterns.…”
Section: Rehabilitation and Afferent Driven Plasticity For Reaching And Graspingmentioning
confidence: 99%
“…In 2018, Keller, et al [173] investigated the EMG patterns in hindlimb muscles of SCI rats that underwent a daily range-of-motion stretching therapy. After several consecutive days of stretching, locomotor ability declined, and EMG recordings revealed increased clonus-like contractions during stretching [173]. This irregular muscle firing due to the stretching may explain the emergence of the irregular stepping patterns.…”
Section: Rehabilitation and Afferent Driven Plasticity For Reaching And Graspingmentioning
confidence: 99%
“…After prenatal HI, rabbit kits exhibit increased excitability of the monosynaptic Hreflex without significant anatomical changes in large diameter, myelinated primary afferent fibers (Synowiec et al, 2019). In other models of nervous system injury, chronic pain is associated with dysfunctional nociceptors that exhibit robust anatomical and electrophysiological plasticity (Dougherty et al, 2004;Bedi et al, 2010;Zhang et al, 2013;Detloff et al, 2014bDetloff et al, , 2016Moy et al, 2018;Shiers et al, 2020;Wangzhou et al, 2021); however, emerging evidence suggests that nociceptive primary afferent input impedes motor output following CNS injury (Keller et al, 2017(Keller et al, , 2018(Keller et al, , 2019. In a series of studies, Keller et al demonstrated that nociceptor depletion reduces muscle contractures and spasticity of the hindlimbs and improves overall locomotor performance following spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“…It could be that these IB4-positive nociceptors are hyperexcitable, and that altered activity, not anatomy, contributes to pain-like behavior in response to mechanical stimuli in HI kits. In other rodent models of nervous system injury, chronic pain and paw hypersensitivity is associated with dysfunctional nociceptors that exhibit robust anatomical and electrophysiological plasticity (Bedi et al, 2010;Detloff et al, 2016Detloff et al, , 2014Dougherty et al, 2004;Moy et al, 2018;Zhang et al, 2013); further, emerging evidence suggests that nociceptive primary afferent input impedes motor output following CNS injury (Keller et al, 2017(Keller et al, , 2019(Keller et al, , 2018. In a series of studies, Keller et al demonstrated that nociceptor depletion reduces muscle contractures and spasticity of the hindlimbs and improves overall locomotor performance following spinal cord injury.…”
mentioning
confidence: 99%
“…EKG is one of the most widespread diagnostic tools in medicine and the similarity between human and rat EKG 8 has permitted the study of various physiological conditions and cardiac diseases 9,10 . Along with EKG signals other surface biopotentials such as sEMG and EEG are studied in rats, analysis of these signals is used in sleep studies, epilepsy, locomotive analysis, and effect of spinal cord injuries 11,12 .…”
Section: State Of the Art In Wireless Biopotential Recordingmentioning
confidence: 99%